The Relationship Between the Ergonomic Factors and the Intention to Leave or Retire in Services Sector - Cardoso, S.; Ramos, S.; Ramalho, N. (Psicologia Social e das Organizações: Métodos, estudos e perspetivas., 2022)
The services sector is becoming increasingly predominant in the labor market but extant research on the services sector highlights psychosocial risk factors, which overshadow the role of ergonomic physical factors. Hence, it is crucial to study both physical and psychosocial ergonomic factors in the services sector as well as their relationship with job outcomes. The aim of this study is to test the relation between ergonomic factors and intent to leave or retire through a four-path sequential mediation model. With a sample of 122 workers from the services sector, we measured physical and psychosocial ergonomic factors, perceived work-related health, health conditions, job satisfaction, and intention to leave or retire. Findings support a partial mediational process in which ergonomic factors are related with the perceived work-related health, which is, in turn, relate to job satisfaction and with intentions to leave or retire. We conclude that physical factors play an important role in the services sector.